Obtaining and Characterization of New Materials, Volume IV (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The fourth volume of this Special Issue, like the first three, covers a wide range of topics, such as obtaining and characterizing new materials, from the nano- to macro-scale, involving new alloys, ceramics, composites, biomaterials, and polymers, as well as procedures and technologies for enhancing their structure, properties, and functions. In order to be able to select the future use of these new materials, we first must understand their structure to understand their characteristics, involving modern techniques such as microscopy (SEM, TEM, AFM, STM, etc.), spectroscopy (EDX, XRD, XRF, FTIR, XPS, etc.), mechanical tests (tensile, hardness, elastic modulus, toughness, etc.), and their behavior (corrosion, thermal—DSC, STA, DMA, magnetic properties, biocompatibility—in vitro and in vivo), among many others.